Digitalisasi dan Penguatan Kelembagaan IKM SriKayu Kota Surakarta: Strategi Kolaboratif Peningkatan Daya Saing Global - Choerudin, Achmad; Ambarwati, Retnoning; Ramadhan, Dwinanda Ripta (Gapenas Publisher, 2025)
This community service program aims to strengthen institutional capacity and enhance the competitiveness of wood-based Small and Medium Industries (SMIs) in Surakarta through a digitalization approach and multi-stakeholder synergy. The program involved industry associations, local government, academics, and local wood entrepreneurs. The methods applied included digital marketing workshops, cooperative institutional assistance, and focus group discussions. The results indicate an increase in participants’ digital literacy, the emergence of multi-stakeholder collaboration commitments, and the formulation of digitalization strategies for wood product marketing and innovation. This article emphasizes the importance of integrating digital technology with cooperative institutions to build the competitiveness of local SMIs in the global market.